Clinical considerations for the treatment of secondary differentiated thyroid carcinoma in childhood cancer survivors. Issue 3 (September 2020) - van Santen, Hanneke M; Alexander, Erik K; Rivkees, Scott A; Frey, Eva; Clement, Sarah C; Dierselhuis, Miranda P; Lebbink, Chantal A; Links, Thera P; Lorenz, Kerstin; Peeters, Robin P; Reiners, Christoph; Vriens, Menno R; et al.
Abstract : The incidence of differentiated thyroid carcinoma (DTC) has increased rapidly over the past several years. Thus far, the only conclusively established risk factor for developing DTC is exposure to ionizing radiation, especially when the exposure occurs in childhood. Since the number of childhood cancer survivors (CCS) is increasing due to improvements in treatment and supportive care, the number of patients who will develop DTC after surviving childhood cancer (secondary thyroid cancer) is also expected to rise. Currently, there are no recommendations for management of thyroid cancer specifically for patients who develop DTC as a consequence of cancer therapy during childhood. Since complications or late effects from prior cancer treatment may elevate the risk of toxicity from DTC therapy, the medical history of CCS should be considered carefully in choosing DTC treatment. In this paper, we emphasize how the occurrence and treatment of the initial childhood malignancy affects the medical and psychosocial factors that will play a role in the diagnosis and treatment of a secondary DTC. We present considerations for clinicians to use in the management of patients with secondary DTC, based on the available evidence combined with experience-based opinions of the authors.